León Felipe’s Poetics of Exodus: an Intertextual Approach to Español del éxodo y del llanto and Ganarás la luz (Castilla. Estudios de Literatura, 2010)
In this study a path is suggested through some texts from two key works by León Felipe, written during his exile, Español del éxodo y del llanto and Ganarás la luz. The aim of this study is not only to show the evolution of topics, symbols, intertextual relationships and forms, from a historical perspective to another one which attempts to emphasize the ethic value of exile as an immanent human condition; in fact, it is also important to underline the presence of such evolution, in embryo, since the moment of primordial poetic creation. The way shown by León Felipe, especially by means of a thick intertextual texture, implies the transformation of the historical paradigm of exile into the poetical and ethical paradigm of exodus, as a sapiential way towards the light.